Perkembangan Motorik Siswa SD Melalui Pembelajaran Penjaskes - Karina Saraswati (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Motor development is an important aspect in the growth and development of elementary school students, one effort that can be made to optimize students' motor development is through Physical Education, Sports, and Health (Penjaskes) learning. This study used a descriptive qualitative. The results showed that Penjaskes learning implemented in a planned, varied, and fun manner can improve students' gross and fine motor skills. The physical development of elementary school-aged children includes coordination of body movements such as running, tiptoeing, jumping, hanging, etc. These activities are necessary to improve gross motor coordination skills. However, motor development at this age becomes smoother and more regular compared to infancy. They appear to run faster and are good at jumping and are able to maintain their body balance. To refine motor skills, children must continue to do physical activities and in addition, children must also be involved in sports activities such as gymnastics, swimming, etc.